Literasi Pemasaran dan Keuangan Berbasis Digital UMKM Sambal Pecel Bu Susy - Khuluqi, Khusnul; Purwasih, Desy; Handayani, Asih (ABDIMAS Iqtishadia, 2023)
Digital-based marketing and financial literacy needs to be developed so that MSMEs are able to maximize digital media to develop their businesses. Implementation of digital-based marketing strategies, namely through social media such as Instagram, Facebook and Tiktok Shop or through marketplaces or e-commerce that can be used as digital marketing, namely through Tokopedia, Shopee, Bukalapak, Lazada, BliBli, and others. As for digital finance that can be used by MSMEs, namely Dana, Ovo, Gopay, Link Aja, Shopee Pay, QRIS, mobile banking, and internet banking. MSME is an independent productive economic enterprise, usually carried out by individuals or business entities that are not subsidiaries or branches of companies that are owned, controlled, or become part directly or indirectly. The business actors in this activity are UMKM Sambal Pecel Bu Susy in the Pamulang Estate Complex.This Community Service activity aims to provide education regarding proper digital-based marketing and financial literacy and implement digital-based marketing and financial strategies to increase the competitiveness of MSMEs. The method developed in this activity was through socialization of digital-based marketing and financial literacy to MSMEs Sambal Pecel Bu Susy. The problems faced by MSME actors are related to a lack of knowledge regarding digital-based marketing and financial literacy in their business so that the implementation of digital-based marketing and financial strategies to increase competitiveness is classified as weak and business development is slow. MSME actors argue that they have no knowledge related to good and proper digital-based marketing and financial literacy. So that with activities regarding the socialization of digital-based marketing and financial literacy, it can provide insight, knowledge, and skills in understanding appropriate digital-based marketing and financial literacy for business actors and can be directly applied in their business.